Model Pengembangan Profesional Guru (Studi Multi Situs Di SMA Negeri 1 Palangka Raya Dan Sma Negeri 4 Palangka Raya) - Eka Mutmainnah; Ahmad Suriansyah; Aslamiah Aslamiah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: Teacher professionalism is a fundamental factor in human resource development, because the quality of education delivered by competent educators contributes directly to the formation of individuals with integrity, knowledge, and adequate skills to face future dynamics and challenges. Based on the results of initial observations, human resource development through teacher professional training is running well through a designed teacher professional development program and transformational leadership roles at SMA Negeri 1 Palangka Raya and SMA Negeri 4 Palangka Raya. This study aims to examine the professional development model that has been carried out at SMA Negeri 1 Palangka Raya and SMA Negeri 4 Palangka Raya. Data collection through interviews, observations and document studies, was analyzed using the Miles & Huberman model through single-site data analysis and cross-site data analysis. The results of the study show that the development strategy designed by this school is effective in responding to the real needs of teachers and providing space for exploration of teaching practices. Teacher involvement appears as a result and condition for the implementation of a meaningful teacher professional development strategy. The results of the study show that transformational leadership has an important role in shaping relevant and adaptive strategies, thus having a direct impact on the success of teacher professional development. This shows that the quality of the principal's leadership, especially in terms of effective communication, appreciation, and support for individual development, is an interrelated factor with the involvement of teachers in the process. It is also recommended that the development of professional teachers be made a sustainable program. This research also opens up space for further research to understand the development of professional teachers in more depth. Keywords: Teacher Professional Development; Teacher Engagement; Instructional Leadership. Abstrak: Profesionalisme guru merupakan faktor fundamental dalam pengembangan sumber daya manusia, karena kualitas pendidikan yang disampaikan oleh tenaga pendidik yang kompeten berkontribusi langsung pada pembentukan individu yang berintegritas, berpengetahuan luas, serta memiliki keterampilan yang memadai untuk menghadapi dinamika dan tantangan masa depan. Berdasarkan hasil observasi awal, pengembangan SDM melalui pelatihan profesional guru yang berjalan dengan baik melalui program pengembangan profesional guru yang dirancang dan peran kepemimpinan transformasional di SMA Negeri 1 Palangka Raya dan SMA Negeri 4 Palangka Raya. Penelitian ini bertujuan untuk menelaah model pengembangan profesional yang sudah dilakukan di SMA Negeri 1 Palangka Raya dan SMA Negeri 4 Palangka Raya. Pengumpulan data melalui wawancara, observasi dan studi dokumen, dianalisis menggunakan model Miles & Huberman melalui analisis data satu situs dan analisis data lintas situs. Hasil penelitian menunjukkan bahwa strategi pengembangan yang dirancang oleh sekolah ini efektif dalam merespon kebutuhan nyata guru dan memberi ruang eksplorasi praktik mengajar. Keterlibatan guru muncul sebagai hasil dan syarat berjalannya strategi pengembangan profesional guru yang bermakna. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional memiliki peran penting dalam membentuk strategi yang relevan dan adaptif, sehingga berdampak langsung pada keberhasilan pengembangan profesional guru. Hal ini memperlihatkan bahwa kualitas kepemimpinan kepala sekolah, khususnya dalam hal komunikasi yang efektif, pemberian apresiasi, serta dukungan terhadap pengembangan individu, menjadi faktor yang saling terkait dengan keterlibatan guru dalam proses tersebut. Disarankan pula agar pengembangan guru professional dijadikan program yang berkelanjutan. Penelitian ini juga membuka ruang bagi penelitian selanjutnya untuk memahami pengembangan guru professional secara lebih mendalam. Kata kunci: Pengembangan Profesional Guru; Keterlibatan Guru; Kepemimpinan Instruksional.